2020
DOI: 10.1002/jum.15583
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐MRI Correlation for Healing of Rotator Cuff Repairs Using Power Doppler, Sonographic Shear Wave Elastography and MR Signal Characteristics

Abstract: Objective To determine whether the healing response in rotator cuff repairs can be quantitatively characterized using a multimodality imaging approach with MR signal intensity, power Doppler and shear wave elastography (SWE). Materials and Methods Patients scheduled for rotator cuff repair were prospectively enrolled between September 2013 and June 2016. A 12 patient cohort with unilateral, full‐thickness, supraspinatus tendon tears underwent MRI and ultrasound both preoperatively and postoperatively (at 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
(66 reference statements)
0
11
1
Order By: Relevance
“…Itoigawa et al 27 examined the tendon at the anteromedial anchor insertion in patients who underwent double‐row rotator cuff repairs, whereas all repairs in this study, and 10/12 repairs in the Nocera et al 26 study used a single‐row inverted mattress configuration. A single‐row inverted mattress repair likely subject the tendon areas measured under load, whereas areas in‐between medial and lateral anchors in the double‐row configuration may not be under load.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Itoigawa et al 27 examined the tendon at the anteromedial anchor insertion in patients who underwent double‐row rotator cuff repairs, whereas all repairs in this study, and 10/12 repairs in the Nocera et al 26 study used a single‐row inverted mattress configuration. A single‐row inverted mattress repair likely subject the tendon areas measured under load, whereas areas in‐between medial and lateral anchors in the double‐row configuration may not be under load.…”
Section: Discussionmentioning
confidence: 88%
“…Best et al 25 Several studies have evaluated tendon stiffness post-rotator cuff repair using shear wave elastography. Nocera et al 26 reported that SWE stiffness of the repaired supraspinatus tendon at its insertion on the greater tuberosity increased in 12 human patients, 6 months post-rotator cuff repair using the Siemens ACUSON S3000 HELIX Evolution ultrasound system (Siemens Medical Solutions, Mountain View, CA). Itoigawa et al 27 measured SWE stiffness of repaired tendons at the site of the anteromedial anchor insertion at 1 week, and monthly from 1 to 6 months postoperatively in 60 human patients who underwent double-row rotator cuff repair using the Aixplorer system: Version 9.2 (SuperSonic Imagine, Aix-en Prevence, Cadex, France), and found that the SWE stiffness of the repaired tendon was greatest at 1 week postoperatively, reduced by 15% at 1 month, then stabilized out to 6 months.…”
Section: Found Thatmentioning
confidence: 99%
“…Nocera et al determined the healing response after RC repairs using a multimodality imaging approach with MRI, power Doppler and SWE ( 12 ). They evaluated 12 patients with unilateral, full-thickness, supraspinatus tendon tear in a cohort study with preoperative and postoperative (at 3 and 6 months post-operation) US and MRI.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning recently published shoulder SE articles, shoulder capsulitis showed increased stiffness in supraspinatus and infraspinatus tendons and CHL on SWE evaluation ( 14 ). For fatty infiltration assessment and correlation with MRI grading, two recent studies with different conclusions and further studies seem necessary ( 5 , 12 ). One study showed a softer supraspinatus tendon after 60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Nocera et al 31 identified that the SWE stiffness of the repaired supraspinatus tendon increased over time post rotator cuff repair. However, the results reported by Nocera et al 31 did not achieve statistical significance, which may be due to the study's small sample size (n = 12) and short postoperative follow-up of 6 months. Itoigawa et al 30 conducted a temporal SWE study assessing the stiffness of the healing supraspinatus tendon at 1 week and monthly from 1 to 6 months post rotator cuff repair.…”
Section: Discussionmentioning
confidence: 99%